2017
DOI: 10.1103/physrevb.95.165411
|View full text |Cite
|
Sign up to set email alerts
|

Universality of thermal transport in amorphous nanowires at low temperatures

Abstract: Thermal transport properties of amorphous materials at low temperatures are governed by the interaction between phonons and localized excitations referred to as tunneling two-level systems (TLSs). The temperature variation of the thermal conductivity of these amorphous materials is considered as universal and is characterized by a quadratic power law. This is well described by the phenomenological TLS model even though its microscopic explanation is still elusive. Here, by scaling down to the nanometer-scale a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…This is illustrated in Fig. 3b , where the measurements are compared to the different expected regimes of heat conduction at low temperature: boundary-limited heat transport (the Casimir regime) characterized by a cubic behavior in temperature (black line), and the quantum limit of fully ballistic transport characterized by a linear regime (dark blue line) only when the transmission coefficients are equal to one; the light blue line is a simple quadratic fit likely to describe thermal transport in amorphous materials like SiN when phonons are predominantly scattered by two level systems (TLS) 34 38 ; in amorphous materials atoms or group of atoms may tunnel between two different equilibrium positions creating what is called a TLS. As it is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is illustrated in Fig. 3b , where the measurements are compared to the different expected regimes of heat conduction at low temperature: boundary-limited heat transport (the Casimir regime) characterized by a cubic behavior in temperature (black line), and the quantum limit of fully ballistic transport characterized by a linear regime (dark blue line) only when the transmission coefficients are equal to one; the light blue line is a simple quadratic fit likely to describe thermal transport in amorphous materials like SiN when phonons are predominantly scattered by two level systems (TLS) 34 38 ; in amorphous materials atoms or group of atoms may tunnel between two different equilibrium positions creating what is called a TLS. As it is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, this is not the only possible origin for this thermal resistance. It has been shown recently that, in amorphous nanostructures, the phonon-TLS scattering is the limiting mechanism for phonon transport in the diffusive regime 38 . As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Adapted from Leivo andPekola, 1998, andLeivo, 1999. temperatures of ∼0.1 K fall about 1 order of magnitude below the quantum value, and the temperature dependence of thermal conductance is close to T 2 . Tavakoli et al (2017Tavakoli et al ( , 2018 proposed nonballistic transmission in their bridges as the origin of their results. Finally, experiments by Zen et al (2014) demonstrated that thermal conductance can be strongly suppressed even in two dimensions with proper patterning of the membranes into a nanostructured periodic phononic crystal.…”
Section: Quantum Noise Of a Resistormentioning
confidence: 97%
“…The latter experiment measuring the temperature of the GaAs platform in the middle using N-I-S tunnel junctions demonstrated Debye thermal conductance at T ≫ 100 mK but tended to follow the expected quantum thermal conductance at the lowest temperatures. In the more recent experiments by Tavakoli et al (2017Tavakoli et al ( , 2018 the measurement on submicronwide silicon nitride bridges was made differential in the sense that there was no need to add superconducting leads on these phonon-conducting legs. The results at the lowest κ ≃ 14.5T 1.98 mW m −1 K −1 for the full membrane and κ ≃ 1.58T 1.54 and 0.57T 1.37 mW m −1 K −1 for 25and 4-μm-wide bridges, respectively, where T is expressed in kelvins.…”
Section: Quantum Noise Of a Resistormentioning
confidence: 99%
“…The latter experiment measuring the temperature of the GaAs platform in the middle using NIS tunnel junctions demonstrated Debye thermal conductance at T 100 mK, but tended to follow the expected quantum thermal conductance at the lowest temperatures. In the more recent experiments by (Tavakoli et al, 2017(Tavakoli et al, , 2018 the measurement on sub-micron wide silicon nitride bridges was made differential in the sense that there was no need to add superconducting leads on these phonon-conducting legs. The results at the lowest temperatures of ∼ 0.1 K fall about one order of magnitude below the quantum value, and the temperature dependence of thermal conductance is close to T 2 .…”
Section: Quantum Noise Of a Resistormentioning
confidence: 99%